The effect of hypnotherapy and mental toughness on concentration when competing for futsal athletes - Rachmi Marsheilla Aguss; Rizki Yuliandra (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2021)
The purpose of this study was to determine the difference in the effect of the type of hypnosis and the level of mental toughness on the concentration of futsal athletes. This research method is experimental. Types of hypnotherapy that are done are hypnosis and self-hypnosis. The data collection technique used a questionnaire, the variable measured mental toughness was low and a little low using, questionnaire and hypnotherapy treatment with 6 meetings with a duration of 30-60 minutes, grouping the level of mental toughness was obtained after pretesting the results of the questionnaire. The data analysis technique was two way anava with SPSS 16. The subjects of the research were 16 male futsal athletes. The significance level is 0.05. The results showed that there were differences in the effect of hypnosis and self-hypnosis on the athlete's concentration, the significance value = 0.013, meaning that there was an effect. There is no difference in the effect of low and rather low mental toughness on the athlete's concentration, the significance value = 0.130 means there is no effect. There is no interaction between mental toughness and hypnotherapy on the athlete's concentration, the significance value = 0.635 means mental toughness and hypnotherapy do not interact. The conclusions of the study are getting the differences in the treatment of hypnosis and self-hypnosis, knowing the differences in the effect of mental toughness, and knowing the interaction between hypnotherapy and mental toughness. The advice is that athletes have good mental toughness and self-control, believe in their own abilities. Coaches support athletes by providing coaching that can improve mental toughness and concentration. PENGARUH JENIS HIPNOTERAPI DAN TINGKAT KETANGGUHAN MENTAL TERHADAP KONSENTRASI ATLET FUTSAL AbstrakTujuan dari penelitian ini adalah untuk mengetahui perbedaan pengaruh jenis hipnosis dan tingkat ketangguhan mental terhadap konsentrasi atlet futsal. Metode penelitian ini eksperimen. Jenis hipnoterapi yang dilakukan adalah hipnosis dan self-hipnosis. Teknik pengumpulan data menggunakan angket, variabel yang diukur ketangguhan mental rendah dan agak rendah dengan menggunakan angket ketangguhan mental dan treatment hypnotherapy dengan 6 peretemuan durasi 30-60 menit, pengelompokkan tingkat ketangguhan mental diperoleh setelah diadakan pretest hasil dari angket tersebut. Teknik analisis data two way anava dengan program SPSS 16. Subjek penelitian atlet futsal putra berjumlah 16 orang. Taraf signifikasi 0,05. Hasil penelitian yaitu ada perbedaan pengaruh hipnosis dan self-hypnosis terhadap konsentrasi atlet, nilai signifikansi = 0,013, artinya ada pengaruh. Tidak ada perbedaan pengaruh ketangguhan mental rendah dan agak rendah terhadap konsentrasi atlet nilai signifikansi = 0,130 berarti tidak ada pengaruh. Tidak ada interaksi antara ketangguhan mental dan hipnoterapi terhadap konsentrasi atlet, nilai signifikansi = 0,635 artinya ketangguhan mental dan hipnoterapi tidak berinteraksi. Simpulan penelitian yaitu mendapatkan perbedaan perlakuan hipnosis dan self-hipnosis, diketahuinya perbedaan pengaruh ketangguhan mental, dan diketahuinya interaksi antara hipnoterapi dan ketangguhan mental. Sarannya atlet memiliki ketangguhan mental dan kontrol diri yang baik, percaya pada kemampuan sendiri. Pelatih mendukung atlet dengan memberikan pembinaan yang dapat meningkatkan ketangguhan mental dan konsentrasi.